Analyzing the Impact of Regulatory Policies on Financial Stability and Market Dynamics in the Banking Industry - Ahmad Abiyan Karem; Malika Saida Azzahra (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2024)
This research delves into the intricate relationship between regulatory policies and the banking industry, aiming to uncover the multifaceted implications of regulatory frameworks on bank behavior, market dynamics, and economic outcomes. Through a comprehensive review of existing literature, empirical analysis, and theoretical frameworks, this study provides valuable insights into the effectiveness, challenges, and implications of regulatory interventions in shaping the banking sector. The research findings reveal that regulatory policies exert a significant influence on bank behavior and risk management practices. Capital adequacy requirements, liquidity standards, and risk management guidelines play a crucial role in enhancing banks' financial resilience, reducing the likelihood of insolvency, and mitigating systemic risks. Moreover, regulatory interventions impact market structure, competition, and innovation within the banking industry, with implications for consumer outcomes and financial stability. Overall, this research contributes to a deeper understanding of the complexities of banking regulation and informs evidence-based policymaking and regulatory reforms. By fostering collaboration, innovation, and regulatory effectiveness, stakeholders can work together to build a resilient, inclusive, and sustainable banking sector that serves the needs of society and the economy at large.